Fruit bioactive compounds: Effect on lactic acid bacteria and on intestinal microbiota - Borgonovi, Tais Fernanda [UNESP]; Virgolin, Lara Borghi [UNESP]; Janzantti, Natália Soares [UNESP]; Casarotti, Sabrina Neves; Penna, Ana Lúcia Barretto [UNESP] (Elsevier, 2022)
The benefits of bioactive compounds to human health have been highly explored in recent years; they are widely distributed in nature, mainly in fruits. In this review, the effect of the main fruit bioactive compounds (FBC) on lactic acid bacteria (LAB) and on gut microbiota composition was discussed. The fruit dietary fibers, phenolic compounds, fatty acids, carotenoids, and vitamins have important health benefits. Furthermore, they can interact with LAB and modulate the human intestinal microbiota, which favor the diversity of beneficial bacterial groups, thus providing several benefits to human health, such as reducing weight gain, improving the mucosal barrier function of gastrointestinal (GI) tract against pathogens, decreasing chronic inflammation and incidence of diseases, such as cardiovascular ones, diabetes, hypertension and chronic diseases. Additionally, FBC are able to change the Firmicutes/Bacteroidetes ratio and inhibit the putrefactive bacteria in the gut. Due to the complex composition of human gut microbiota and variations among individuals, additional research must be carried out to elucidate the mechanism of interaction between the bioactive compounds and the human microbiota.
Keywords: Functional food; Health benefit; Immunomodulation; Intestinal health; Prebiotics